The Influence of Visual Merchandising, E-WoM, Discounts, and Hedonic Shopping Motivation on Impulse Buying Mr. DIY Consumers in Purwokerto - Yanti Dwi Saputri; Mayla Surveyandini; Akbar Pahlevi (ProBisnis : Jurnal Manajemen, 2025)
This type of research is quantitative research using a survey method. The population in this study consists of consumers who shop at Mr. DIY stores in Purwokerto, the number of which is unknown. The minimum sample size was determined using the Lemeshow formula, and questionnaires were distributed to 110 respondents using accidental sampling. The analysis tool used was multiple linear regression analysis. The analysis results showed that the adjusted R2 value was 53.1%, and the t-test proved that visual merchandising, e-wom, discounts, and hedonistic shopping motivation had a positive and significant partial effect on impulse buying among Mr.DIY consumers in Purwokerto. This study implies that Mr. DIY needs to ensure that the window display remains clean, bright, and neatly arranged, and ensure that promotional product signs are clearly written. Mr. DIY must increase consumer trust and purchasing interest. Mr. DIY can manage discounts with a well-thought-out strategy, such as offering discounts at certain times or for certain products only. Mr. DIY Purwokerto should adjust its marketing and promotion strategies to attract customers. For further researchers with similar topics, they can add other independent variables or mediating or moderating variables.